A Detection Method for Text Steganalysis Using Evolution Algorithm (EA) Approach - Puriwat, Lertkrai (2012)
The ability of sending a secret message through a network nowadays has become a more challenging and complex process. One of the reasons why we need tools to detect the hidden message is because of security and safety. Secret messages can be both for good or bad, and subversive groups have been known to send secret messages to coordinate their terrorist activities. Thus,a technique such as steganalysis is one method example to detect a secret message. Much of the technical steganalysis work had been carried out on image, video, and audio steganalysis, but in any agency or organisation, all business documents generally uses the natural language in text form or document form. Therefore, this research employed a detection factor based on the evolution algorithm method for text steganalysis. The aim of this project was to detect a hidden message in an observed message using text steganalysis.